2003
DOI: 10.1046/j.1467-2494.2003.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

The cornified cell envelope: an important marker of stratum corneum maturation in healthy and dry skin

Abstract: The cornified cell envelope (CE) formed by transglutaminase-mediated epsilon-(gamma-glutamyl)lysine cross-linking of specialized corneocyte proteins is the most insoluble component of the terminally differentiated keratinocyte. Under normal Nomarski optics, two types of CE are readily distinguishable: an irregularly shaped, readily deformed 'fragile' envelope (CEf), which predominates in the deepest layers of the stratum corneum, and a polygonal "resilient" or 'rigid' envelope (CEr), which represents over 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 31 publications
3
77
0
3
Order By: Relevance
“…These stresses can be significant and can result in chapping and cracking. Such damage can compromise the barrier function, resulting in detrimental skin reactions including inflammation, infection, scarring, abnormal desquamation and further aggravate skin disorders such as atopic dermatitis, ichthyosis vulgaris and chronic xerosis [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These stresses can be significant and can result in chapping and cracking. Such damage can compromise the barrier function, resulting in detrimental skin reactions including inflammation, infection, scarring, abnormal desquamation and further aggravate skin disorders such as atopic dermatitis, ichthyosis vulgaris and chronic xerosis [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The surface area of facial corneocytes is smaller, resulting in a shorter path-length for molecular transport and a noticeably higher permeability (19,20). In addition, the face is one of the first body sites affected when atopic dermatitis (AD) develops and the ratio of fragile to mature corneocytes is higher here than on the inner upper arm (21). Voegeli et al (22) have also demonstrated higher levels of desquamation-related proteases on the face.…”
Section: Introductionmentioning
confidence: 99%
“…Although the SC is typically a highly efficient barrier, exposure to harsh conditions can alter its function, leading to severe skin damage such as chapping and cracking. Such damage can cause detrimental skin responses including inflammation and infection caused by compromised barrier function, scarring, and abnormal desquamation, and further aggravate the effects of skin disorders such as atopic dermatitis, ichthyosis vulgaris, and chronic xerosis (4)(5)(6)(7).…”
mentioning
confidence: 99%